Improving specialist palliative care discharges from hospitals and hospices to community settings: a qualitative interview study of the communication experiences of patients, carers, and primary care professionals - Katharine Weetman; Catherine Grimley; Cara Bailey; Celia J. Bernstein; Jeremy Dale; Aprella Fitch; Sarah Mitchell; Rumandeep Tiwana; John I. MacArtney (BMC Palliative Care)
Abstract Background Patients who have received specialist intervention during periods of complex symptom and palliative care needs (e.g. pain crisis) may be discharged from specialist palliative care services to primary care. Despite such discharges being reasonably common, little is known about what happens during this process. We sought to explore patient, carer and healthcare professional experiences, identifying ways to improve this crucial and time-sensitive part of the healthcare journey. Methods A qualitative interview study designed using an interpretive approach and reflexive thematic analysis methods. Sampling was purposive across six specialist palliative care sites (hospitals and hospices) and six general practices. Results A total of 38 participants took part in interviews:15 patients, 8 carers and 15 primary care professionals. Two overarching key themes were developed. The first described the multiple ways that ‘discharge’ was understood depending on the setting and circumstances of the patient. The second explored what was associated with better or worse transitions to primary care. Discharge communications that were accurate and complete were described as effective whereby written information reinforced verbal instructions and acted as a reminder. Participant suggestions for improving these discharge communications included: incorporating the patient’s palliative care preferences (e.g. advanced directives); offering letters to patients and, where appropriate, carers; providing post-discharge follow-up and contact details; ensuring medication instructions are accessible to patients and carers. Conclusions Current specialist palliative care discharge communications risk confusion, distress, and increased workload post-discharge. The study identified numerous suggestions professionals could take to improve this process. Trial registration Registered in ISRCTN Registry on 29.12.2023 ref: ISRCTN18098027.